2021
DOI: 10.3390/nano11051224
|View full text |Cite
|
Sign up to set email alerts
|

Layered LiCoO2–LiFeO2 Heterostructure Composite for Semiconductor-Based Fuel Cells

Abstract: Enabling fast ionic transport at a low-temperature range (400–600 °C) is of great importance to promoting the development of solid oxide fuel cells (SOFCs). In this study, a layer-structured LiCoO2–LiFeO2 heterostructure composite is explored for the low-temperature (LT) SOFCs. Fuel cell devices with different configurations are fabricated to investigate the multifunction property of LiCoO2–LiFeO2 heterostructure composites. The LiCoO2–LiFeO2 composite is employed as a cathode in conventional SOFCs and as a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…With respect to the research and development of desirable electrolytes, recent studies have revealed that the use of BaCeO 3 and BaZrO 3 -based proton conductors, oxygendeficient semiconductors, composite materials, and the reduction of YSZ thickness by thin film techniques are feasible approaches, which result in modest decreases in the operating temperature of SOFCs down to 500-700 • C [6][7][8][9][10][11]. Particularly, semiconductor ionic materials and composite have been used to develop electrolytes to enable high ionic conductivity at low temperatures of 300-500 • C. These semiconductor electrolytes realize their electrolyte functionality via various semiconductor properties and conduction mechanisms, which are different from that of traditional electrolytes such as YSZ and Sm 0.2 Ce 0.8 O 1.9 (SDC) that primarily rely on cation substitution to create oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the research and development of desirable electrolytes, recent studies have revealed that the use of BaCeO 3 and BaZrO 3 -based proton conductors, oxygendeficient semiconductors, composite materials, and the reduction of YSZ thickness by thin film techniques are feasible approaches, which result in modest decreases in the operating temperature of SOFCs down to 500-700 • C [6][7][8][9][10][11]. Particularly, semiconductor ionic materials and composite have been used to develop electrolytes to enable high ionic conductivity at low temperatures of 300-500 • C. These semiconductor electrolytes realize their electrolyte functionality via various semiconductor properties and conduction mechanisms, which are different from that of traditional electrolytes such as YSZ and Sm 0.2 Ce 0.8 O 1.9 (SDC) that primarily rely on cation substitution to create oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the research and development of desirable electrolytes, recent studies have revealed that the use of BaCeO 3 and BaZrO 3 -based proton conductors, oxygen-deficient semiconductors, composite materials, and the reduction of YSZ thickness by thin film techniques are feasible approaches, which result in modest decreases in the operating temperature of SOFCs down to 500–700 °C [ 6 , 7 , 8 , 9 , 10 , 11 ]. Particularly, semiconductor ionic materials and composite have been used to develop electrolytes to enable high ionic conductivity at low temperatures of 300–500 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic conductors used in single-layer cells are mostly based on pure doped ceria, and composites of doped ceria and alkali carbonates. The electrode materials used in single-layer cells include LiCoO 2 -LiFeO 2 [ 10 ], Ni 0.8 Co 0.15 Al 0.05 LiO 2 [ 11 ], La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ [ 12 ], CuFe 2 O 4 [ 13 , 14 ], Li 0.15 Ni 0.25 Cu 0.1 Zn 0.2 Fe 0.3 O x [ 15 ], Li 0.3 Ni 0.6 Cu 0.07 Sr 0.03 O 2-δ [ 16 ], Sr 2 Fe 1.5 Mo 0.5 O 6-δ [ 17 ], Li 0.15 Ni 0.45 Zn 0.4 O 2 [ 18 ], etc. In addition, proton conductors (BaCe 0.7 Zr 0.1 Y 0.2 O 3-δ ) have been used in single-layer cells [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tremendous efforts have been dedicated to reduce the production cost and promote the performance of the cell based on functional materials and the revolutionary design of the structure of SOFCs [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In recent years, SOFCs based on a ceramic proton conductor–also known as protonic ceramic fuel cells (PCFCs)–have demonstrated outstanding performance.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the new architectures in heterostructure materials with a semiconductor and an ionic conductor yield interesting properties with ionic conduction highways between two-phase interfaces [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. A notable example is CeO 2 /CeO 2-δ core-shell structure, which exhibits a super proton conductivity of 0.16 S cm −1 for the electrolyte at 520 °C [ 11 ].…”
Section: Introductionmentioning
confidence: 99%